Cs2TiBr Solar Cell Performance Enhancement by Different Absorber Layer Thickness - Saleh K. Mezaal; Nadeem. K. Hassan (مجلة جامعة الانبار للعلوم الصرفة, 2021)
Cs2TiBr6 is a promising material as an Absorber layer of Solar cell. Further studies showed that this compound is more stable, and possess an appropriate electrical and optical properties. The compound of (FTO/V2O5/Cs2TiBr6/CdTe) is simulated for the first time in this work by using the Solar Cell Capacitance Simulator (SCAPS-1D) program and the obtained transformation efficiency (η) was (10.09) with (0.5µm) of (Cs2TiBr6) thickness. The effect of (Cs2TiBr6) thickness was studied in this paper used different variations of absorber layer thickness (0.5 – 4.0 μm). Solar cell enhanced by absorber layer thickness showed (18.17 mA/cm2, 0.924V, and 86.58%) (Jsc, Voc, FF) respectively which led to increase of transformation efficiency (η) from (10.09 % to 14.55%).